Job characteristics and work engagement among secondary school teachers: the moderating role of co-worker support - Vincent K. Kibambila (African Business Management Journal)
This study examines the moderating effect of co-worker support on the relationship between job characteristics and employee work engagement among secondary school teachers in Tanzania. A cross-sectional research design was adopted; data were collected using a structured questionnaire from 221 randomly selected respondents, and analysis was carried out using structural equation modelling. The findings indicate that job characteristics have a positive and significant relationship with employee work engagement (β = 0.478, p = 0.001). Additionally, the moderating effect of co-worker support on the relationship between job characteristics and employee work engagement is positive and significant (β = 0.305, p = 0.046). Conversely, the findings indicate that the relationship between co-worker support and employee work engagement is not statistically significant (β = 0.217, p = 0.067). These findings have implications for theory and management, suggesting that managers in the education sector should prioritise fostering a supportive atmosphere among teachers and encouraging mutual assistance and collaboration. This can create a work environment where employees feel valued and empowered, leading to increased job satisfaction and engagement. The study aligns with the job characteristics model, highlighting that job characteristics promote positive outcomes like relationship-building, teamwork, and employee retention. It recommends evaluating jobs to improve their features, making them more attractive and rewarding, which increases employee engagement. Additionally, ambiguous and less attractive jobs should be redesigned to minimise anxiety and stress.